BROKEN TEXT EFEKTIVITAS STRATEGI PEMBELAJARAN BROKEN TEXT TERHADAP HASIL BELAJAR MATA PELAJARAN BAHASA ARAB PADA KELAS VIII DI MTSN 10 NGAWI TAHUN AJARAN 2023/2024: EFEKTIVITAS STRATEGI PEMBELAJARAN BROKEN TEXT TERHADAP HASIL BELAJAR MATA PELAJARAN BAHASA ARAB PADA KELAS VIII DI MTSN 10 NGAWI TAHUN AJARAN 2023/2024 - Prayitno , Reno Aji; Santoso, Nur Cholis Agus; Mustain, Mustain (University of Darussalam Gontor, 2024)
The Arabic language is rich in linguistic styles, and among these is the style of Qashr. When comparing this style with the grammatical rules of the Indonesian language, we find that the Indonesian language also possesses a Qashr style. This study aims to identify the similarities and differences in the style of Al Qashr between Arabic and Indonesian, focusing on how to construct the style of Al Qashr, as well as to know how to teach the style of Al Qashr in Arabic. The research also uses the contrastive descriptive method and to collect data on the subject of shortening, data collection tools were used, documentation and observation, through Arabic and Indonesian grammar books, balaghah book and university journals from the two languages. To analyze the data obtained, the researcher used the method of constrastive analysis. The result of this research are three: 1) What is agreed upon in the two languages, such as the style of Al Qashr with innama, lakin, bal, and taqdim haqqahu takhir 2) What is specific to Arabic, such as the style of Al Qashr with la, an-nafyu and al-istisna’ 3) What is specific to Indonesian. And how to teach the style of Al Qashr in Arabic begins with the style agreed upon between the two languages, such as the style of Al Qashr with the word innama and bal lakin and the presentation of what is due to delay in Arabic. After that, they move to teaching the style of shortening specific to Arabic.